CHARACTERIZATION OF TENSIBLE STRENGTH PROPERTIES OF LAMINATED PARTICLES OF SLIM SHELL PARTICLES/E-GLASS USING POLYESTER MATRIX - Kusairi, Kusairi; Nayiroh, Nurun (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
The increasing number of traditional boats made from wood can cause the forest to be deforested. Besides, it also results in scarcity and an increase in the price of basic wood materials so that production costs are increasingly expensive—also, the factors of decay by mould, heating, weathering. One of the efforts that can be made in the traditional shipbuilding process is through making boats made from cheap and high-quality E-Glass fibre laminate composite boards. The purpose of this study was to determine the effect of volume composition of E-glass fibres and scallop shell particles on the tensile strength of hybrid composites. Making hybrid composites by mixing scallop shell filler, E-Glass fibre and matrix. Percentage volume fraction 0C: 0E, 10C: 20E, 15C: 15E and 20C: 10E. The results showed that the maximum tensile strength at the volume fraction of 10C: 20E was 34.15567 MPa, this result was higher than the maximum requirements set by BSN in 2006, namely 0.304 MPa. The existence of a strong bond between the fibres and the matrix can increase the tensile strength of the composite as well as the influence of the scallop shell particles which can help the matrix to accept external loads/stresses so that the composite strength increases.